Pemberdayaan Orang Tua dalam Pencegahan Stunting melalui Pendidikan Kesehatan tentang Akupresur ST 36 (Zusanli) dan SP 6 (Sanyinjiao) - Dewi Kartika Sari; Fredlina Rossa Balindra; Nadia Taqqiya (Abdibaraya, 2026)
Stunting remains a public health problem influenced by poor appetite in children. Prevention efforts can be implemented through parental empowerment using skill-based health education, such as acupressure. This community service program aimed to improve parents’ knowledge and skills in performing acupressure at ST 36 (Zusanli) and SP 6 (Sanyinjiao) points. The methods included socialization, pretest, health education, practical training, and posttest involving 40 parents of toddlers in Blimbingsari Village. The results showed an improvement in both knowledge and skills. The Wilcoxon test yielded a p-value of 0.000 (<0.05), indicating a significant difference between the pre- and post-intervention scores. Health education with a hands-on approach was effective in enhancing parents’ abilities. Acupressure can serve as a simple and practical intervention for family-based stunting prevention